Plasma insulin, serum lipids and lipoproteins in gall stone disease in non-insulin dependent diabetic subjects: a case control study. Issue 3 (March 1990) - Laakso, M; Suhonen, M; Julkunen, R; Pyörälä, K
Abstract : Fasting insulin, lipids and lipoproteins were measured in 22 middle aged female non-insulin dependent diabetics with gall stone disease (cases) and in 22 non-insulin dependent diabetics without gall stone disease (controls). The groups were matched for sex, age, obesity, and fasting glucose concentrations. No differences were observed between the cases and controls in duration of diabetes, glycated haemoglobin A1, alcohol intake, smoking, use of cardiovascular drugs or a history of myocardial infarction. Diabetics with gall stone disease had higher fasting insulin concentrations (p less than 0.5), lower total (p less than 0.01) and low density lipoprotein cholesterol (p less than 0.01) and high density lipoprotein cholesterol (not statistically significant) concentrations than diabetics without gall stone disease. These changes in insulin, lipids and lipoproteins are similar to reported changes in non-diabetic subjects with gall stone disease. Therefore, they are characteristic for gall stone disease and not as such explanatory to an increased risk of gall stones in patients with non-insulin dependent diabetes.